OPTIMIZATION OF BURNING PRODUCTION PROCESS OF CERAMSITE WITH SPECIFIED DENSITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The paper goes into peculiarities of using developed mathematical models of ceramsite burning and computational models created on their basis. The work is done in the light of analysis and synthesis of multivariate control system of kiln angular velocity and kiln charge with volumetric thermal capacity burners. It is shown that computational models of burning as an object of control are problem-oriented on producing ceramsite with specified density. Mathematical model of ceramsite burning process as an object with distributed parameters is synthesized. The transition from model with distributed parameters to the mode with lumped parameters is performed. Then the authors used a model with three bearing cross-sections along Z-axis in Matlab software and created a computational model of multivariate object of control with inter-channel connections. The paper presents experimental computational set up methods and methods of ceramsite burning optimal curve identification on the criterion of minimizing energy consumption for burning. The developed method of staging computational experiments makes it possible to predict the strength of ceramsite if values of control actions are known. The results of modeling help create methodology of choosing optimal modes of ceramsite burning with the required mark of strength and with minimum energy consumption.